2020
DOI: 10.1002/brb3.1852
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐suppressed and tissue‐fraction corrected metabolic distributions in human central brain structures using 2D 1H magnetic resonance spectroscopic imaging at 7 T

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 65 publications
3
20
1
Order By: Relevance
“…Comparison with the literature is difficult, as most studies report intra-subject T A B L E 8 Comparison of this study's metabolite ratios and standard deviations of tCho, Glu, Glu + Gln, NAA + NAAG, Ins + Gly, and GSH to tCr in six ROIs compared with similar 7 T MRSI results of Reference. 70 The results of our study are consistently higher for all except GSH/tCr, with two higher/lower/same ratio regions each or inter-system CVs, such as van de Bank et al, 68 who reported CVs for SVS on four different 7 T systems in the posterior cingulate cortex of 3-4% for NAA, tCho, tCr, mIns, and Glu, 22.2% for GABA, 14.4% for GSH, and 8.8% for Gln. Another example, but at 3 T, is the study by Zhang et al, 73 who calculated intra-subject CVs for whole-brain EPSI in 10 volunteers over three scans in 47 ROIs and found NAA CVs of 3.3%-17.8%, tCho CVs of 3.7%-31.0%, tCr CVs of 3.1%-18.0% (with mean ROI CVs < 10%), and mIns CVs of 5.9%-54.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with the literature is difficult, as most studies report intra-subject T A B L E 8 Comparison of this study's metabolite ratios and standard deviations of tCho, Glu, Glu + Gln, NAA + NAAG, Ins + Gly, and GSH to tCr in six ROIs compared with similar 7 T MRSI results of Reference. 70 The results of our study are consistently higher for all except GSH/tCr, with two higher/lower/same ratio regions each or inter-system CVs, such as van de Bank et al, 68 who reported CVs for SVS on four different 7 T systems in the posterior cingulate cortex of 3-4% for NAA, tCho, tCr, mIns, and Glu, 22.2% for GABA, 14.4% for GSH, and 8.8% for Gln. Another example, but at 3 T, is the study by Zhang et al, 73 who calculated intra-subject CVs for whole-brain EPSI in 10 volunteers over three scans in 47 ROIs and found NAA CVs of 3.3%-17.8%, tCho CVs of 3.7%-31.0%, tCr CVs of 3.1%-18.0% (with mean ROI CVs < 10%), and mIns CVs of 5.9%-54.0%.…”
Section: Discussionmentioning
confidence: 99%
“…The production of metabolite maps registered to standardized brain atlases, such as the MNI152 brain atlas, is required to facilitate group-based statistical analysis (Bhogal et al, 2020) or to analyze spectroscopic data along with other MR images, such as arterial spin labeling (ASL) MRI (Cengiz, et al, 2017, Cengiz, et al, 2018. FSL-MRS, Osprey, and MRSpant co-register MRS data onto the reference anatomical MRI to compute the CSF fraction and correct for it, but they currently do not support metabolite map generation, registration onto a common brain atlas, and ROI analysis.…”
Section: Discussionmentioning
confidence: 99%
“…MRSI methodology was used as previously published. 24 In short, data were acquired using a 7 tesla MR scanner (Phillips, Best, NL) equipped with a dual-transmit head coil and 32-channel receive coil (Nova Medical, Wilmington Ma, USA). Second order image-based shimming was performed for all acquisitions.…”
Section: Methodsmentioning
confidence: 99%
“…Full spectral reconstruction and post-processing as well as metabolite map and quality assurance map generation details as previously published. 24 Region of interest masks of brain regions from which sufficient coverage was attained (i.e. the Caudate, Putamen, Thalamus and Pallidum) were generated using MNI tissue fraction maps ( Figure 1A ) using FSL (FMRIB).…”
Section: Methodsmentioning
confidence: 99%